Ion channel regulation by phosphoinositides analyzed with VSPs – PI(4,5)P2 affinity, phosphoinositide selectivity, and PI(4,5)P2 pool accessibility - Rjasanow, Alexandra; Leitner, Michael G.; Thallmair, Veronika; Halaszovich, Christian R.; Oliver, Dominik (Frontiers in Pharmacology, 2015)
The activity of many proteins depends on the phosphoinositide (PI) content of the membrane. E.g., dynamic changes of the concentration of PI(4,5)P2 are cellular signals that regulate ion channels. The susceptibility of a channel to such dynamics depends on its affinity for PI(4,5)P2. Yet, measuring affinities for endogenous PIs has not been possible directly, but has relied largely on the response to soluble analogs, which may not quantitatively reflect binding to native lipids. Voltage-sensitive phosphatases (VSPs) turn over PI(4,5)P2 to PI(4)P when activated by depolarization. In combination with voltage-clamp electrophysiology VSPs are useful tools for rapid and reversible depletion of PI(4,5)P2. Because cellular PI(4,5)P2 is resynthesized rapidly, steady state PI(4,5)P2 changes with the degree of VSP activation and thus depends on membrane potential. Here we show that titration of endogenous PI(4,5)P2 with Ci-VSP allows for the quantification of relative PI(4,5)P2 affinities of ion channels. The sensitivity of inward rectifier and voltage-gated K+ channels to Ci-VSP allowed for comparison of PI(4,5)P2 affinities within and across channel subfamilies and detected changes of affinity in mutant channels. The results also reveal that VSPs are useful only for PI effectors with high binding specificity among PI isoforms, because PI(4,5)P2 depletion occurs at constant overall PI level. Thus, Kir6.2, a channel activated by PI(4,5)P2 and PI(4)P was insensitive to VSP. Surprisingly, despite comparable PI(4,5)P2 affinity as determined by Ci-VSP, the Kv7 and Kir channel families strongly differed in their sensitivity to receptor-mediated depletion of PI(4,5)P2. While Kv7 members were highly sensitive to activation of PLC by Gq-coupled receptors, Kir channels were insensitive even when PI(4,5)P2 affinity was lowered by mutation. We hypothesize that different channels may be associated with distinct pools of PI(4,5)P2 that differ in their accessibility to PLC and VSPs.